DINAMIKA IDEOLOGI KARMAN DALAM NOVEL KUBAH KARYA AHMAD TOHARI BERDASARKAN PERSPEKTIF SOSIOLOGI SASTRA MARXISME - Basid, Abdul; As Sulthoni, Zahrah Nida' Rosyida (Jurnal Pendidikan Bahasa dan Sastra, 2018)
This study aims to analyze the dynamics of ideology that occurred on the main character named Karman in a novel ‘Kubah’ by Ahmad Tohari. The analysis uses Marx's literary sociology theory which focuses on the grouping of society classes based on their infrastructure and superstructure in literary works. The exposure analysis includes; (1) discussion of ideological conceptualization, (2) discussion of Marx's sociology of novel ‘Kubah’ paradigm of social class structure relation in society which include: (a) the analysis of the social class structure of literature, i.e. identification of social background into the context of the occurrence, identification of social classes, the analysis of social activities that occur among social classes represented in interrelated relations, and (b) the literary social class structure relation with the social class structure of society. Based on the analysis, we would discover the form, cause, and impact of Karman's ideological dynamics on Pegaten society.